Students' Mental Health: The Urgency of Pedagogical Interventions and Nurturing Learning Environment Design - Rosi, Fathor; Agus Nu'man; Firdaus Roning (EDUCARE: Jurnal Ilmu Pendidikan, 2025)
This study aims to examine the urgency of pedagogical interventions and the design of a nurturing learning environment in strengthening students’ mental health in secondary schools. The increasing phenomenon of psychosocial disorders such as stress, anxiety, and academic burnout demands an educational approach that is not only cognitive, but also affective and emotional. This study uses a qualitative approach with an exploratory case study design conducted in two secondary schools that have implemented a student well-being-based learning approach. Data collection techniques include in-depth interviews, participant observation, and documentation, which are analysed using the Miles and Huberman interactive model. The results of the study show three main findings: (1) the role of teachers as emotional mediators contributes significantly to creating a healthy psychological climate, (2) the design of a nurturing learning environment increases students’ emotional resilience, and (3) there is a lack of integration between formal school policies and pedagogical practices on mental health issues. The implications of this study indicate the need for educational policy reform that integrates socio-emotional aspects systematically in the curriculum, teacher training, and indicators of learning success. This study recommends strengthening teacher capacity in socio-emotional competencies and developing a more inclusive, ecosystem-based education model that emphasises emotional well-being.